A Study of Tourist Attraction Development Policy and Environmental Conservation in the Ijen Crater Natural Park - Aditya Wiralatief Sanjaya; Masetya Mukti; Ayu Wanda Febrian; Holkiyah Novitasari (Universitas Airlangga, 2019)
Tourism development in Indonesia is increasing, as it is beneficial to the the social, cultural, educational, environmental and economic sectors of the country. In maintaining the sustainability of tourism, the government optimizes business in the field of ecotourism. Ecotourism as an environmentally friendly tourism can have a positive impact in the form of economic improvement, conservation, education, environmental preservation and empowerment of local communities. One ecotourism that has always been a magnet for tourists today is the Nature Tourism Park (TWA) Ijen Crater. Ijen Crater is a nature conservation area with diverse natural potential and is used as a nature conservation park. This study discusses the analysis of environmental damage prevention in the Ijen Crater Nature Park. A qualitative descriptive research approach with data collection techniques through primary data and secondary data was applied. The data were analyzed with data collection analysis, reduction, presentation and data verification. The results of this study are the natural potential of Ijen Crater TWA including the Ijen crater lake, blue fire, sulfur mining, vegetation and animals, Paltuding fun trekking, and Bunder cottage. The environmental conditions of tourist objects and attractions in Ijen Crater TWA are still in a good stage because the manager continues to strive to supervise and protect the tourist objects and attractions. The results of the analysis were interpreted by applying literary research of two regulations, namely UU No.32 of 2009 and UU No.10 of 2009. The result showed that there were three indicators that were not in accordance with UU No.10 of 2009 on Tourism, including the implementation of principles; coordination; and rights, obligations and prohibitions. The efforts to prevent enviromental damage can be done by dividing the area blocks, designing the site and disseminating information to tourists.